Description Of Mothers' Motivation In Developmental Stimulation Of Children Aged 1 - 3 Years Old In - Rista Dian Anggraini; Wahyu Anjas Sari (Jurnal Ilmiah Kesehatan, 2021)
Children will grow faster when their mother stimulate their development. But in fact, parents' awareness is still low due to parents' reluctance. They believe that stimulation is for children with developmental delay. This research aims to describe the mothers' motivation in the developmental stimulation of children aged 1-3 years old in Sambungrejo Village District Sidoarjo. This study used a descriptive design. The population was mothers with children age 1–3 years in Sambungrejo Village Sukodono Sidoarjo. There were 50 respondents with simple random sampling. The research variable was mothers' motivation in the developmental stimulation of children aged 1-3 years. The instrument utilized a questionnaire. The data analysis was frequency distribution. The results showed that 62,5% of respondents had low motivation, while 37,5% of respondents had a high motive to perform stimulation in developing children aged 1–3. The study concludes that most mothers have low motivation in developmental stimulation. Health workers should give health education about the developmental stimulation of children to mothers.